The Influence of Plants as Absorption of Particles and Noise In Ambient Air In Yogyakarta City - Naris Dyah Prasetyawati; Sigid Sudaryanto; Heru Ardianto; Aulia Ramadhan (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2026)
Background: Air is a basic and primary need for living things. Good air contains the element oxygen in sufficient quantities. Oxygen plays an important role in the body's metabolic processes. Oxygen deficiency will cause hypoxia and fatal conditions can cause death. Good air pollution standard index When it has a level of less than 50, the lower the value, the better the air quality in an environment. Environmental problems related to air quality have now reached a disturbing stage and are a priority to be addressed immediately. Sources of pollutants in the ambient air, among others, are due to human activities. The urbanization of the population and industry are the two main sources that are thought to reduce air quality to a low level. All control efforts are currently being carried out, starting from control at the source to the environment and efforts to protect the living things affected. This study aims to determine the traffic density and the influence of various types of plants along the main road on the levels of dust and noise in the ambient air of the city of Yogyakarta. Method: This research is qualitative research using observational research methods supported by a literature review. Results: The results of the study show that the traffic density in the city of Yogyakarta fluctuates a lot but tends to be high. Traffic density has an impact on noise and dust levels in the ambient air of Yogyakarta City. Conclusion: The recommended air pollution control effort is to control the second node of the existing pollution control node. The intervention is carried out in the vehicle (ambient air), this is because the pollutants are already in the environment so an effective and efficient control model can be carried out in the ambient air environment by utilizing plants as green open spaces.